2018
DOI: 10.18291/njwls.v8is3.105275
|View full text |Cite
|
Sign up to set email alerts
|

Communication in the Digital Work Environment: Implications for Wellbeing at Work

Abstract: This article examines digital communication in the workplace and its association with wellbeing at work. The analysis is based mainly on workshop discussions and is complemented with log data (N = 36). Content analysis was applied to the workshop discussions, while the log data were analyzed by quantifying frequencies. Six themes were found to affect wellbeing at work: the volume of digital communication, expectations of constant connectivity, the quality of the messages, adaptation of new tools, technical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 20 publications
6
62
1
Order By: Relevance
“…Hence, although distant work was considered to decrease interaction and communication in the negative stories, it was also valued because of its potential to provide opportunities for job control. Previous studies have found that the asynchrony and increased flexibility offered by digitalization blurs the boundary between work and leisure time and causes difficulties to disconnect from work (e.g., Bordi et al 2018;Vuori et al 2018). Interestingly, participants of our study viewed the opportunity to flexibly combine work and non-work domains as mostly something positive and supporting professional development (e.g., participation in professional online networks and courses regardless of time and place).…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Hence, although distant work was considered to decrease interaction and communication in the negative stories, it was also valued because of its potential to provide opportunities for job control. Previous studies have found that the asynchrony and increased flexibility offered by digitalization blurs the boundary between work and leisure time and causes difficulties to disconnect from work (e.g., Bordi et al 2018;Vuori et al 2018). Interestingly, participants of our study viewed the opportunity to flexibly combine work and non-work domains as mostly something positive and supporting professional development (e.g., participation in professional online networks and courses regardless of time and place).…”
Section: Discussionmentioning
confidence: 66%
“…However, the increased access to information may also lead to information overload, i.e., "a feeling of being overwhelmed by the quantity of incoming information and the need to respond to it" (O'Driscoll et al 2010, p. 275). Consequently, asynchronous communication and the increased accessibility and availability have been found to facilitate the spillover of work to leisure time (Bordi et al 2018). For instance, previous research has found that employees clear and check their email in the evenings and weekends in order to manage their work-related communication load and their overall workload (Barley et al 2011;Bordi et al 2018).…”
Section: Digitalization Of Workmentioning
confidence: 99%
See 3 more Smart Citations